Vitamin profiling of soybean variety from hills of Uttarakhand - Tina K; Manu Pant; Arvind Singh Negi; Pankaj Nainwal (Environment Conservation Journal)
Uttarakhand is a hilly state in the western Himalayan region where climatic conditions are suitable for agriculture. Since ancient times, the region has grown 'Bhat', a soybean landrace known for its health benefits. The high altitudinal regions prominently feature 'Bhat' in their cuisine, as the extreme weather conditions necessitate energy-rich food. However, there is limited information on the exact nutritional content of this crop. The objective of this work was to evaluate the vitamin profiling, including vitamin B complex and vitamin E, in ‘bhat’ genotypes from different villages of the Pauri Garhwal region of Uttarakhand. The vitamin analysis was carried out through the UPLCMS technique for both water- and fat-soluble vitamins. The analysis revealed Vitamin E to be the most significant vitamin, with the highest concentration of 96.67 mg/kg in one of the samples. Significant differences were obtained in the vitamin content in the samples, indicating the influence of geographical location. The study also highlights the significance of the soybean variety from Uttarakhand as a potential source of both vitamin B and vitamin E.